"Horses for Courses" and "Thin Blue Lines": Community Policing in Transitional Society - Mike Brogden (Police Quarterly 2005; 8; 64, 2005)
The export of policing models from the West has a long history. Current export Processes are dominated by the transfer of community policing (COP) models from Anglo-American jurisdictions to societies currently regarded as undergoing a transitional process. The latter are frequently characterized by rising recorded crime rates and a delegitimation of their own police institutions. Consequently, COP appears to offer a welcome respite, especially when encouraged not just by policing missionaries from the West and donor cash but also by a variety of nongovernmental organizations that see COP effectiveness as a human rights resolution to police abuse. Using secondary data from a range of failed and transitional societies, this article challenges the motives, processes, and consequences of the export of such a Western policing model. The end result, from the preliminary evidence, seems to be one of deepening social schism in the country of import. COP is irrelevant to many such societies.